Her Dream Home : Domesticity and Gender in Advertising in Arts & Architecture = El Hogar de sus Sueños: domesticidad y género en la Publicidad de Arts & Architecture - Díez Martínez, Daniel (Cuaderno de Notas, 2021)
AbstractIn the United States, with the end of World War II, a cultural and territorial model based on the suburban lifestyle took root. Women had taken an active role during the conflict, but postwar American society returned them to the background, restricting them to the care of family and home. The domestic space became again a distinctly female ecosystem. From a gender perspective this article explores how the discourse on housewives and domesticity was expressed in the specialized press, particularly in advertisements published in Arts & Architecture. It tries to show how advertising contributed to the association drawn between women and the domestic sphere, and in particular to the idea of the kitchen as an inherently feminine space. Women were mostly assigned an ornamental role as passive consumers, but occasionally they were portrayed as experts capable of instructing architects on how to design the home.ResumenEl final de la Segunda Guerra Mundial consolidó en Estados Unidos un modelo cultural y territorial basado en el estilo de vida suburbano. Aunque las mujeres habían tenido un papel activo durante el conflicto, la sociedad estadounidense de posguerra las relegó a una posición secundaria limitada a las tareas de cuidado familiar y del hogar, por lo que el espacio doméstico se convirtió en un ecosistema netamente femenino. El objetivo de este artículo consiste en estudiar cómo se estructuró este discurso en la prensa especializada utilizando los anuncios de la revista Arts & Architecture. Se muestra cómo la publicidad contribuyó a la asociación entre la mujer y el ámbito doméstico, y en particular a definir la cocina como un espacio inherentemente femenino. A las mujeres se les asignó principalmente un papel ornamental como consumidoras pasivas, aunque ocasionalmente también aparecían como expertas capaces de instruir a los arquitectos sobre cómo diseñar una casa.